(untitled) (Baghdad Science Journal, 2024)
One technique used to prepare nanoparticles material is Pulsed Laser Ablation in Liquid (PLAL), Silver Oxide nanoparticles (AgO) were prepared by using this technique, where silver target was submerged in ultra-pure water (UPW) at room temperature after that Nd:Yag laser which characteristics by 1064 nm wavelength, Q-switched, and 6ns pulse duration was used to irradiated silver target. This preparation method was used to study the effects of laser irradiation on Nanoparticles synthesized by used varying laser pulse energy 1000 mJ, 500 mJ, and 100 mJ, with 500 pulses each time on the particle size. Nanoparticles are characterized using XRD, SEM, AFM, and UV-Visible spectroscopy. All the structural peaks determined by the XRD test can be indexed as face-centered cubic (FCC) type, the stronger crystalline orientation is located in the (111) plane. The nanoscale particles have an almost spherical shape as inferred from the SEM images. In (1000) mJ laser pulse energy the best smallest particle size was produced. According to AFM results of all films, the particle size 32.45nm, 64.3nm, and 67.86nm respectively for 1000 mJ, 500 mJ, and 100 mJ , the surface roughness affected and increased as increase the laser energy because the increase particle size and aggregation of partials. UV-Visible spectroscopy measured the absorbance of the silver nanoparticle prepared which is increased as increase pulsed laser ablation energy at wavelength 440 nm.